Genetic Diversity and Population Structure of Canarium tramdenum Dai and Yakovl. in Northern Vietnam - Phi Hong Hai; Nguyen Thi Huyen; Ha Thi Huyen Ngoc; Tran Thi Thu Ha; Nguyen Thi Viet Ha; La Anh Duong; Pham Huu Thuong; Alice Muchugi; Le Son (Bogor Agricultural University, Indonesia, 2022)
Canarium tramdenum occurs naturally in subtropical and tropical regions of Indochina and China. The wood is used for making high quality furniture and the fruit and leaves are used in traditional medicine. However, a lack of information on genetic diversity and population structure has handicapped the genetic conservation and domestication of this high-value species. This study evaluated genetic variation within and among four C. tramdenum populations. Sixty individuals were collected from four natural populations in Vietnam in the provinces of Ninhbinh, Bacgiang, Nghean, and Backan. Genetic diversity and genetic structure were determined using 20 ISSR markers. A total of 192 DNA fragments with sizes ranging from 110 bp to 3,000 bp were detected, of which 154 segments (80.2%) were polymorphic and 38 segments (19.8%) were monomorphic. The ISSR data indicated a moderate degree of genetic diversity for the species (h = 0.252). The four populations were separated into three genetic clusters with low levels of genetic distance between them. AMOVA result showed that most (78%) of the genetic variation was within the populations. The moderate to high genetic diversity of C. tramdenum and the low genetic differentiation among populations suggested that all existing natural populations in the particular regions needed to be preserved to protect the genetic diversity of this species.